Clinical, histopathological and parasitological follow-up of dogs naturally infected by Leishmania infantum before and after miltefosine treatment and associated therapies - Amábilli de Souza Rosar; Carolina Leite Martins; Álvaro Menin; Carolina Reck; Edmundo Carlos Grisard; Glauber Wagner; Mário Steindel; Patricia Hermes Stoco; Patricia Flavia Quaresma (PLoS ONE, 2025)
In Brazil, Visceral Leishmaniases is caused by Leishmania infantum, and domestic dogs are the main reservoirs in its urban transmission cycle. As an alternative to euthanizing dogs, miltefosine has been used to treat canine visceral leishmaniasis since 2016. In this study, we have assessed the efficacy of miltefosine for treating canine visceral leishmaniasis in a new endemic area through follow-up of naturally infected dogs was evaluated. The clinical, parasitological, and histopathological characteristics of 21 dogs naturally infected with L. infantum were assessed at three time points: on the day before initiating miltefosine treatment (T0), immediately after treatment completion (T1), and 6 months after treatment completion (T2). Three dogs were treated exclusively with miltefosine, while eighteen received combination therapy with miltefosine with other treatments such as allopurinol, domperidone and immunotherapy. Skin biopsies were obtained from the abdomen to assess inflammatory responses and to quantify parasite loads using qPCR. The parasites were isolated using aspirates acquired from popliteal lymph nodes. Molecular and parasitological analyses confirmed the presence of L. infantum in all dogs, validating the effectiveness of skin and lymph node samples for diagnosis. The clinical conditions of the infected animals were improved and the skin parasite load decreased after treatment, even when distinct combination therapies were performed. The histopathological assessment revealed a miltefosine-induced reduction in the inflammatory response and a decrease in amastigotes number. Furthermore, a positive correlation was established between the reduction in parasite load and the enhancement of clinical scoring, as well as a reduction in the skin inflammatory response. Our findings suggest that miltefosine-based combination therapies reduce skin parasite load and improve clinical outcomes, while the dogs treated with miltefosine alone showed increased parasitic load and worsened clinical staging at T2. Considering this data belonging to a recent transmission area, treatment strategy suggests effective in controlling canine visceral leishmaniasis.